The Role of the Arabic Language in Tourism Service Quality: A Study of Tourism Services at Najaf Airport (The Peerian Journal, 2025)
This study analyzes the pivotal role of the Arabic language in enhancing the quality of tourism services, focusing on the services provided at Najaf International Airport, which is a major gateway to a city with a unique religious and cultural status in the Islamic world. The study aims to reveal the extent to which linguistic accuracy and communicative efficiency, whether written on signboards and documents or spoken in direct interaction between service providers and visitors, affect visitors’ perceptions of the overall quality of their experience. The study also seeks to diagnose the strengths and weaknesses of the current linguistic reality at the airport, based on the hypothesis that the Arabic language constitutes a fundamental element in the identity and spirit of the service, and is not merely a tool for transmitting information. The study relies in its methodology on linking the theoretical framework based on the components of service quality in modern administrative literature and the functional and aesthetic characteristics of the Arabic language, and descriptive field analysis based on the questionnaire directed to visitors and employees, and direct observation. This research comes to fill a gap in the academic literature, which rarely addresses the organic relationship between language and service quality in the tourism sector, especially in Sensitive religious and cultural contexts, seeking to provide an applied vision that contributes to advancing linguistic practices to meet contemporary challenges and future aspirations of the Iraqi tourism sector.